Hypereutectoid steel in early medieval sword production in Europe - Paweł Kucypera; Jiří Hošek (Fasciculi Archaeologiae Historicae, 2014)
Hypereutectoid steel is viewed as a material of exceeding quality for the manufacture of swords, providing keen edges and strong bodies to their blades. A significant group of weapons, where such material was used, comprises some swords from the “Ulfberht” family. It is suggested that these specimens were made using crucible steel, a high-carbon material produced in the territories of Central Asia and India. The article presents in short other examples of European swords, where hypereutectoid steel was identified, and discusses different methods for its production known at the time, possibilities in discerning between them, problems with working with such a material, as well as the resulting limitations and shortcomings. The issues are considered from the archaeometallurgical point of view, with archaeological data, material analyzes and experimental studies serving as the background